Extracellular matrix protein expression is brain region dependent. Issue 7 (1st February 2016) - Dauth, Stephanie; Grevesse, Thomas; Pantazopoulos, Harry; Campbell, Patrick H.; Maoz, Ben M.; Berretta, Sabina; Parker, Kevin Kit
ABSTRACT: In the brain, extracellular matrix (ECM) components form networks that contribute to structural and functional diversity. Maladaptive remodeling of ECM networks has been reported in neurodegenerative and psychiatric disorders, suggesting that the brain microenvironment is a dynamic structure. A lack of quantitative information about ECM distribution in the brain hinders an understanding of region‐specific ECM functions and the role of ECM in health and disease. We hypothesized that each ECM protein as well as specific ECM structures, such as perineuronal nets (PNNs) and interstitial matrix, are differentially distributed throughout the brain, contributing to the unique structure and function in the various regions of the brain. To test our hypothesis, we quantitatively analyzed the distribution, colocalization, and protein expression of aggrecan, brevican, and tenascin‐R throughout the rat brain utilizing immunohistochemistry and mass spectrometry analysis and assessed the effect of aggrecan, brevican, and/or tenascin‐R on neurite outgrowth in vitro. We focused on aggrecan, brevican, and tenascin‐R as they are especially expressed in the mature brain, and have established roles in brain development, plasticity, and neurite outgrowth. The results revealed a differentiated distribution of all three proteins throughout the brain and indicated that their presence significantly reduces neurite outgrowth in a 3D in vitro environment. These results underline the importance of a unique and complex ECM distribution for brain physiology and suggest that encoding the distribution of distinct ECM proteins throughout the brain will aid in understanding their function in physiology and in turn assist in identifying their role in disease. J. Comp. Neurol. 524:1309–1336, 2016. © 2016 Wiley Periodicals, Inc. Abstract : The authors identified a brain region–specific distribution of ECM proteins, suggesting the existence of a complex and tightly controlled network with specific functions of this network in distinct brain regions. In turn, this information provides a basis to identify ECM alterations in disease and the consequences thereof.